Association between pre-and postnatal growth and longitudinal trends in serum uric acid levels and blood pressure in children aged 3 to 7 years - Bomi Park; Bohyun Park; Hye Ah Lee; Seonhwa Lee; Hyejin Han; Eunae Park; Su Jin Cho; Hae Soon Kim; Young Ju Kim; Eun-Hee Ha; Hyesook Park (BMC, 2020)
Abstract Background Uric acid has been identified as an important factor in the development of hypertension. If low birth weight (LBW) combined with catch-up growth (CUG) is associated with continuously elevated serum uric acid levels (SUA) level trajectories, LBW children who experience CUG may have an increased risk of hypertension later in life. Therefore, this cohort study analyzed longitudinal trends in SUA levels and changes in blood pressure in relation to pre- and postnatal growth over an extended follow-up period. Methods This prospective cohort study of 364 children from the Ewha Birth and Growth Cohort assessed the effects of pre- and postnatal growth status on SUA at 3, 5, and 7 years of age using a linear mixed model and the change in blood pressure over the 7-year follow-up period using a generalized linear model (analysis of covariance). CUG was defined as a change in weight (between birth and age 3) with a z-score > 0.67 for LBW subjects. The multivariate model considered sex, gestational age, and uric acid, height, and weight at 3 years of age. Results Children with LBW and CUG had higher SUA for the first 7 years of life compared to the normal birth weight group. This trend was particularly evident when comparing LBW children at term to children with normal birth weight. Within the group with LBW at term, children with greater CUG had higher SUA than children with normal birth weight, and this difference increased with age. Changes in the systolic blood pressure between 3 and 7 years of age were higher by 7.9 mmHg in children who experienced LBW and CUG compared with those who had a normal birth weight after adjusting for sex, gestational age, and height, weight, and uric acid at 3 years of age (p-value = 0.08). Conclusions The uric acid levels and changes in systolic blood pressure were consistently higher among LBW children who experienced CUG compared with NBW children for the first 7 years of life. LBW children who experienced greater weight gain from birth to age 3 had even higher uric acid levels compared with NBW children.